The Reading Desk: Supporting Lightweight Note-Taking in Digital Documents - Jen Pearson (Research and Advanced Technology for Digital Libraries, 2011)
When reading on paper, readers often write notes, fold corners or insert bookmarks without apparent conscious effort. Research into digital reading has discovered that electronic tools are far less intuitive, require significantly more attention, and are much less used. This paper introduces “The Digital Reading Desk” – a document reading interface that enhances existing digital reading interactions by adopting effective elements of paper interaction, and combining those with digital enhancements.